Measurement of local crystal lattice strain variations in dealloyed nanoporous gold. Issue 1 (2nd January 2018) - Mahr, Christoph; Müller-Caspary, Knut; Graf, Matthias; Lackmann, Anastasia; Grieb, Tim; Schowalter, Marco; Krause, Florian F.; Mehrtens, Thorsten; Wittstock, Arne; Weissmüller, Jörg; Rosenauer, Andreas
ABSTRACT: Reversible macroscopic length changes in nanoporous structures can be achieved by applying electric potentials or by exposing them to different gases or liquids. Thus, these materials are interesting candidates for applications as sensors or actuators. Macroscopic length changes originate from microscopic changes of crystal lattice parameters. In this report, we show spatially resolved measurements of crystal lattice strain in dealloyed nanoporous gold. The results confirm theory by indicating a compression of the lattice along the axis of cylindrically shaped ligaments and an expansion in radial direction. Furthermore, we show that curved npAu surfaces show inward relaxation of the surface layer. GRAPHICAL ABSTRACT: IMPACT STATEMENT We show spatially resolved measurements of strain in nanoporous gold confirming theory: Crystal lattice is compressed along the axis of cylindrical ligaments and expanded in radial direction, surfaces relax inward.